Supervised Neighborhood Play (SNP) Service Delivery by an international non-government organization through its implementing partners in Quezon, Bicol, and Metro Manila - Floresca, Marlene S.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This study explored the implementation of Supervised Neighborhood Play (SNP) as initiated by an international non-government organization through its Implementing Partners (IP). Specifically, this study aimed to describe the (1) criteria in the selection of the SNP location; (2) delivery of SNP sessions; (3) strategies of Volunteer SNP Facilitators for parent and family involvement; and, (4) involvement of Local Social Welfare and Development Offices in the implementation of the SNP service. This is a qualitative research that employed both Descriptive and Exploratory methodological approaches. Key informant interviews and non-participatory observation were used for data collection. Thirty (30) of the total 65 Volunteer SNP Facilitators in urban and rural settings were purposively selected as respondents. Four LSWDO representatives from the sample sites also participated in the study. Results revealed that selection criteria for SNP site included safety, space, proximity to children, and sanitation. SNP sessions were conducted for 10 months, at least thrice a week, each session held for at least two hours. Each SNP site catered to an average of 15 children aged 2 to 4 years old. Volunteer SNP Facilitators received continuous capacity-building activities organized by the IPs operating in their areas. This assisted them in the development and delivery of developmentally appropriate SNP curriculum. Involvement of parents and families in implementation of SNP was central to voluntary services, while LSWDO and LGU's involvement depended on the level of their understanding and appreciation of the program which varied from awareness to adoption of the program. While SNP service delivery in both rural and urban areas has no significant variation, the difference lies on the physical setting which is more favorable for the rural areas. Collaboration among different community stakeholders like public agencies and private organizations will assist in the improvement of SNP service delivery. In addition, the academe and research institutions may play a critical role in building evidences as to the social impact of SNP and capacity-building of Volunteer SNP Facilitators, hence strengthening the foundation of complementary and alternative programs for marginalized young children.
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman
Keywords: Child care services -- Philippines -- Quezon Province; Child care services -- Philippines -- Bicol; Child care services -- Philippines -- Metro Manila